Have a go! - Broome, Errol; Australia. Curriculum Development Centre (Canberra : Curriculum Development Centre, 1988)
A book featuring the stories of how Aboriginal and other Australian sportspeople became famous; includes a photo of the Aboriginal cricket team who toured England in 1868.
For primary school students.
White, K. Bibliography of Australian children's books
Keywords: Sports -- Australia -- Juvenile literature; Athletes -- Australia -- Juvenile literature; Sport; Australia